If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + -2)(-5x + 6) = 0 Reorder the terms: (-2 + 7x)(-5x + 6) = 0 Reorder the terms: (-2 + 7x)(6 + -5x) = 0 Multiply (-2 + 7x) * (6 + -5x) (-2(6 + -5x) + 7x * (6 + -5x)) = 0 ((6 * -2 + -5x * -2) + 7x * (6 + -5x)) = 0 ((-12 + 10x) + 7x * (6 + -5x)) = 0 (-12 + 10x + (6 * 7x + -5x * 7x)) = 0 (-12 + 10x + (42x + -35x2)) = 0 Combine like terms: 10x + 42x = 52x (-12 + 52x + -35x2) = 0 Solving -12 + 52x + -35x2 = 0 Solving for variable 'x'. Factor a trinomial. (-6 + 5x)(2 + -7x) = 0Subproblem 1
Set the factor '(-6 + 5x)' equal to zero and attempt to solve: Simplifying -6 + 5x = 0 Solving -6 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 5x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 5x = 0 + 6 5x = 0 + 6 Combine like terms: 0 + 6 = 6 5x = 6 Divide each side by '5'. x = 1.2 Simplifying x = 1.2Subproblem 2
Set the factor '(2 + -7x)' equal to zero and attempt to solve: Simplifying 2 + -7x = 0 Solving 2 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -7x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -7x = 0 + -2 -7x = 0 + -2 Combine like terms: 0 + -2 = -2 -7x = -2 Divide each side by '-7'. x = 0.2857142857 Simplifying x = 0.2857142857Solution
x = {1.2, 0.2857142857}
| a^2+14a-99=0 | | -2m-5m=9m-12 | | 7n+1=2n-4 | | -x+19+3x+19=4 | | 50+2x=120-5x | | 24+8=24+2x | | 7y-4=-14 | | u(u^4-13u^2+36)=0 | | 11+m=m-.25 | | x+1=12+3x | | u(u^4-13u^2+63)=0 | | 8a-5a=3a | | 24+2x=24+8 | | 13.4=8.5-x | | -12x+3(x-5)=6-2x | | 24+8x=24+2 | | 2(n+1)+2=3n-4 | | 8x^2-2xy+7y^2=4 | | 5p-55=a | | c=1.50+0.75h | | 11+5y=2y+8 | | 32x-7=19x-7 | | x^2-xy-6y^2=0 | | 10y^2-12y+7=0 | | 2-3(x-4)=11 | | 2+6h+18=2.4h+22 | | 98+12= | | x+9=2x-1 | | -5n-2+3(2n+1)=4n-3 | | 2a-3=25 | | 2p*3=12p*2 | | 8n=n-90 |